Children's representational strategies based on verbal versus bodily interactions with music: an intervention-based study. (1st January 2020) - Fortuna, Sandra; Nijs, Luc
ABSTRACT: Can a bodily engagement with music affect the process of musical meaning formation and, as such, affect children's graphic representation of music? To address this question a comparative study was conducted in which primary school children ( n  = 52; age = 9–10) without any formal music education participated in a verbal-based (describe the music verbally) vs. movement-based (showing the music in movement) intervention. Before and after the intervention, children were asked to create a graphical representation (drawing) of the music and to provide a verbal explanation of the drawing in relation to the music. Two kinds of graphically representing the music have been considered: differentiated, capturing one or more musical parameters, and global, based on narrative and metaphorical interpretation. A McNemar test revealed a significant increase of differentiated representations from pre-test and post-test among children involved in a bodily music interaction with a focus on the temporal organisation of the piece. The children's representational strategies, closely connected to the body articulation, provide relevant insights into the role of body articulation on children's music mental image.